MANAJEMEN HIBAH UNTUK OPTIMALISASI PENGELOLAAN DATA HIBAH DISKOMINFO TABANAN - I Kadek Peri Arta Wijaya; I Gede Santi Astawa; Ida Ayu Gde Suwiprabayanti Putra (Jurnal Pengabdian Informatika, 2026)
Grant data management in government institutions often faces challenges due to inefficient manual processes. This study aims to develop a web-based grant management information system designed to enhance efficiency, transparency, and accuracy in managing grant data at the Department of Communication and Information Technology (Diskominfo) Tabanan. The methods employed include system introduction, usage tutorials, and system launching. The results indicate that this system can facilitate a more integrated grant data management process, allowing users to easily add, edit, delete, and export data. In conclusion, the implementation of this system can significantly optimize grant data management.